High Dietary Salt Intake Is Associated With Histone Methylation in Salt-Sensitive Individuals - Liao, Yueyuan; Chu, Chao; Yan, Yu; Wang, Dan; Ma, Qiong; Gao, Ke; Sun, Yue; Hu, Jiawen; Zheng, Wenling; Mu, Jianjun (Frontiers in Nutrition, 2022)
High salt diet is one of the important risk factors of hypertension and cardiovascular diseases. Increasingly strong evidence supports epigenetic mechanisms’ significant role in hypertension. We aimed to explore associations of epigenetics with high salt diet, salt sensitivity (SS), and SS hypertension. We conducted a dietary intervention study of chronic salt loading in 339 subjects from northern China in 2004 and divided the subjects into different salt sensitivity phenotypes. A total of 152 participants were randomly selected from the same cohort for follow-up in 2018 to explore the effect of a high-salt diet on serum monomethylation of H3K4 (H3K4me1), histone methyltransferase Set7 and lysine-specific demethylase 1 (LSD-1). Among SS individuals, the blood pressure (SBP: 140.8 vs. 132.9 mmHg; MAP: 104.2 vs. 98.7 mmHg) and prevalence of hypertension (58.8% vs. 32.8%) were significantly higher in high salt (HS) diet group than in normal salt (NS) diet group, but not in the salt-resistant (SR) individuals (P>0.05). Serum H3K4me1 level (287.3 vs. 179.7 pg/ml, P<0.05) significantly increased in HS group of SS individuals, but not in SR individuals. We found daily salt intake in SS individuals was positively correlated with serum H3K4me1 (r=0.322, P=0.005) and Set7 (r=0.340, P=0.005) levels after adjusting for age and gender, but not with LSD-1 (r=-0.137, P=0.251). In addition, positive correlation between the serum H3K4me1 level and Set7 level (r=0.326, P=0.007) was also found in SS individuals. These correlations were not evident in SR individuals. Our study indicates that high salt diet increases the serum H3K4me1 and Set7 levels in SS individuals.